Selo combustível social: a perspectiva da indústria de biodiesel do Rio Grande do Sul - Santos, Rozali Araújo dos (2012)
In recent decades, it became more evident concern for sustainable development and environmental preservation, which debate from an individual to a global discussion, including the business. In these terms, the growing concern for the environment and the possible shortage of oil transformed the issue of biofuels to an important topic in Brazil and abroad. In Brazil, aiming to stimulate the production of biofuels, the government created the National Biodiesel Production and Social Fuel Seal, which includes the social dimension of sustainable development, promoting social inclusion of family farmers linked to production activities of oil for the industrialization of biodiesel. In this context, firms can be the primary parts of the strategy proposed by the government, to leveraging sustainable development in Brazil. Given this reality, this study aimed to identify the impact of the Social Fuel Seal in corporate management of south Brazilian companies that decided to adopt this certification, considering the dimensions of sustainable development, innovation and company strategy. To cover the proposed objective, it was used the case study methodology, with a qualitative and descriptive approach. The data was collected through semi-structured interviews, conducted via digital voice recorder, in loco, with a professional with knowledge about the Social Fuel Seal and its management in biodiesel companies that has the Social Fuel Seal certificate, located in the state of Rio Grande do Sul, BsBios, Camera, Granol, Oleoplan e Olfar. In order to support the analysis of this research, it was conducted an assessment tool, used to structure the data collection instrument. The interpretation and data analysis were given mainly in a qualitative approach, using document analysis and content analysis. The results showed that the Social Fuel Seal impacts on businesses in the context of sustainable development, innovation and strategy. The label brings changes for companies and is envisioned as an opportunity for market inclusion. The Social Fuel Seal brings to the companies a competitive advantage in a market still in development, but with good prospects for development and growth.